Locum practice among government medical officers and factors influencing it and the impact on government health services in Negeri Sembilan and Malacca, 1999 - Mohd Anis Haron @ Harun,; Syed Mohamed Aljunid, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross-sectional study using self administered questionnaire on locum practice and I sociodemographic and service factors influencing this practice as well as its effects on productivity and job stress was carried out among all government medical officers in the whole state of Negeri Sembilan and Malacca. Universally chosen samples were made of 335 doctors who hailed from Hospital and Health Divisions and from 154 who responded, only 147 samples were chosen and analyzed in the study. Productivity was measured using 7 productivity indexes and job stress was measured using 'Personal Stress Inventory'. Results revealed that 60.6% of medical officers had practiced locum before and 58.4% of them were still practicing locum during this study, Locum practice were mainly practiced at private clinics (88.5%), after work (94.3%), less than 10 hours a week (69.3%) and for salary supplement (58.1%), whereby, 65.4% of them had managed to earn less than RM 1000. Locum were still being practiced by 51.9% of male medical officers, 41.0% of medical officers aged less than 30 years, 43.4% of medical officers who had served less than 5 years and 55.6% of medical officers who had earned net income less than RM 1 000. t Meanwhile, 80.9% of medical officers who had earned gross income more than : RM 5 000 did not practice locum during the study. Logistic Regression analysis then I revealed that locum practice among medical officers can positively be influenced by sex (male), Malay ethnic, service duration of less than 5 years, Health Division and net income of less than RM 1 000 (p<0.05). Productivity of medical officers, however, could not be influenced by locum practice (p>0.05). No association was I found between locum practice and job stress (p>0.05). Hence, since locum is still being practiced by medical officers to earn extra income, without jeopardizing work productivity or causing job stress, it is suggested that the Ministry of Health should then legalize locum practice. Furthermore, ways to monitor and preparation of guidelines on locum practice should also be looked into.